Computational exploration of two-dimensional silicon diarsenide and germanium arsenide for photovoltaic applications - Matta, Sri Kasi; Zhang, Chunmei; Jiao, Yalong; O'Mullane, Anthony; Du, Aijun (Beilstein Journal of Nanotechnology, 2018)
The properties of bulk compounds required to be suitable for photovoltaic applications, such as excellent visible light absorption, favorable exciton formation, and charge separation are equally essential for two-dimensional (2D) materials. Here, we systematically study 2D group IV–V compounds such as SiAs2 and GeAs2 with regard to their structural, electronic and optical properties using density functional theory (DFT), hybrid functional and Bethe–Salpeter equation (BSE) approaches. We find that the exfoliation of single-layer SiAs2 and GeAs2 is highly feasible and in principle could be carried out experimentally by mechanical cleavage due to the dynamic stability of the compounds, which is inferred by analyzing their vibrational normal mode. SiAs2 and GeAs2 monolayers possess a bandgap of 1.91 and 1.64 eV, respectively, which is excellent for sunlight harvesting, while the exciton binding energy is found to be 0.25 and 0.14 eV, respectively. Furthermore, band-gap tuning is also possible by application of tensile strain. Our results highlight a new family of 2D materials with great potential for solar cell applications.
Keywords: density functional theory (DFT); photovoltaic applications; solar cell; two-dimensional semiconductors

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Dubonos, S. V.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Garcia, J. C.; de Lima, D. B.; Assali, L. V. C.; Justo, J. F. (J. Phys. Chem. C, 2011)

(untitled) - Carvalho, A.; Wang, M.; Zhu, X.; Rodin, A. S.; Su, H.; Castro Neto, A. H. (Nat. Rev. Mater., 2016)

(untitled) - Wadsten, T. (Acta Chem. Scand., 1967)

(untitled) - Rau, J. W.; Kannewurf, C. R. (Phys. Rev. B, 1971)

(untitled) - Panish, M. B. (J. Electrochem. Soc., 1966)

(untitled) - Ugai, Y. A.; Popov, A. E.; Goncharov, E. G.; Tolubaev, K. G. (Zh. Neorg. Khim., 1983)

(untitled) - Hulliger, F.; Mooser, E. (J. Phys. Chem. Solids, 1963)

(untitled) - Wu, P.; Huang, M. (Phys. Status Solidi B, 2016)

(untitled) - Zhao, T.; Sun, Y.; Shuai, Z.; Wang, D. (Chem. Mater., 2017)

(untitled) - Kresse, G.; Furthmüller, J. (Comput. Mater. Sci., 1996)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B, 1996)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Monkhorst, H. J.; Pack, J. D. (Phys. Rev. B, 1976)

(untitled) - Heyd, J.; Scuseria, G. E.; Ernzerhof, M. (J. Chem. Phys., 2003)

(untitled) - Krukau, A. V.; Vydrov, O. A.; Izmaylov, A. F.; Scuseria, G. E. (J. Chem. Phys., 2006)

(untitled) - Mostofi, A. A.; Yates, J. R.; Pizzi, G.; Lee, Y.-S.; Souza, I.; Vanderbilt, D.; Marzari, N. (Comput. Phys. Commun., 2014)

(untitled) - Jiao, Y.; Zhou, L.; Ma, F.; Gao, G.; Kou, L.; Bell, J.; Sanvito, S.; Du, A. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Zhuang, H. L.; Hennig, R. G. (Chem. Mater., 2013)

(untitled) - Singh, A. K.; Mathew, K.; Zhuang, H. L.; Hennig, R. G. (J. Phys. Chem. Lett., 2015)

(untitled) - Bernardi, M.; Palummo, M.; Grossman, J. C. (Nano Lett., 2013)

(untitled) - Yang, L.; Deslippe, J.; Park, C.-H.; Cohen, M. L.; Louie, S. G. (Phys. Rev. Lett., 2009)

(untitled) - Albrecht, S.; Reining, L.; Del Sole, R.; Onida, G. (Phys. Rev. Lett., 1998)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Blöchl, P. E. (Phys. Rev. B, 1994)

(untitled) - Baroni, S.; De Gironcoli, S.; Dal Corso, A.; Giannozzi, P. (Rev. Mod. Phys., 2001)

(untitled) - Giannozzi, P.; Baroni, S.; Bonini, N.; Calandra, M.; Car, R.; Cavazzoni, C.; Ceresoli, D.; Chiarotti, G. L.; Cococcioni, M.; Dabo, I.; Dal Corso, A.; de Gironcoli, S.; et al. (J. Phys.: Condens. Matter, 2009)

(untitled) - Benedict, L. X.; Shirley, E. L.; Bohn, R. B. (Phys. Rev. Lett., 1998)

(untitled) - Onida, G.; Reining, L.; Rubio, A. (Rev. Mod. Phys., 2002)

(untitled) - Rohlfing, M.; Louie, S. G. (Phys. Rev. Lett., 1998)

(untitled) - Rohlfing, M.; Louie, S. G. (Phys. Rev. B: Condens. Matter Mater. Phys., 2000)

(untitled) - Bryden, J. H. (Acta Crystallogr., 1962)

Structural Chemistry of Layer-Type Phases - Hulliger, F. (Springer, 1976)

(untitled) - Singh, A. K.; Hennig, R. G. (Appl. Phys. Lett., 2014)

(untitled) - Cai, Y.; Zhang, G.; Zhang, Y.-W. (Sci. Rep., 2014)

(untitled) - Zhou, M.; Duan, W.; Chen, Y.; Du, A. (Nanoscale, 2015)

(untitled) - Ma, F.; Zhou, M.; Jiao, Y.; Gao, G.; Gu, Y.; Bilic, A.; Chen, Z.; Du, A. (Sci. Rep., 2015)

(untitled) - Conley, H. J.; Wang, B.; Ziegler, J. I.; Haglund, R. F., Jr; Pantelides, S. T.; Bolotin, K. I. (Nano Lett., 2013)

(untitled) - Feng, J.; Qian, X.; Huang, C.-W.; Li, J. (Nat. Photonics, 2012)

(untitled) - Ji, Q.; Zhang, Y.; Gao, T.; Zhang, Y.; Ma, D.; Liu, M.; Chen, Y.; Qiao, X.; Tan, P.-H.; Kan, M.; Feng, J.; Sun, Q.; et al. (Nano Lett., 2013)

(untitled) - Wang, Y. G.; Zhang, Q. L.; Wang, T. H.; Han, W.; Zhou, S. X. (J. Phys. D: Appl. Phys., 2011)

(untitled) - Zhou, L.; Zhuo, Z.; Kou, L.; Du, A.; Tretiak, S. (Nano Lett., 2017)

(untitled) - Tran, V.; Soklaski, R.; Liang, Y.; Yang, L. (Phys. Rev. B: Condens. Matter Mater. Phys., 2014)

(untitled) - Choi, J.-H.; Cui, P.; Lan, H.; Zhang, Z. (Phys. Rev. Lett., 2015)

2016 IEEE 43rd Photovoltaic Specialists Conference (PVSC) - Omelchenko, S. T.; Tolstova, Y.; Atwater, H. A.; Lewis, N. S. (Excitonic effects in photovoltaic materials with large exciton binding energies, Portland, OR, U.S.A., 5.6.2016-10.6.2016, 2016)